Chile : Recent Economic Developments. (IMF Staff Country Reports; Country Report ;, 1996)
This paper examines the sources of growth in Chile and compares Chile's experience with that of other countries. Two alternative measures of the sources of growth for Chile are presented to facilitate comparisons with other studies. The first measure adjusts factor inputs for the degree of utilization (using the unemployment rate), and the second measure introduces an index of the quality of factor inputs. The paper presents estimates of potential output of Chile for 1971-95, and also discusses the projections of potential output growth for Chile over the medium term.